2020
DOI: 10.3390/foods9091329
|View full text |Cite
|
Sign up to set email alerts
|

Modified Atmosphere and Humidity Film Reduces Browning Susceptibility of Oriental Melon Suture Tissue during Cold Storage

Abstract: Oriental melons have a relatively short shelf life as they are harvested during the summer season and susceptible to cold-induced injuries. Typical chilling injury when stored at 4 °C is expressed as browning of the fruit suture. To prolong the shelf life and reduce browning of the fruit, the effects of modified atmosphere packaging (MAP), X-tend modified atmosphere (MA)/modified humidity (MH) bulk packaging (XF), and polyethylene (PE) packaging, on oriental melons were investigated during storage at 4 °C and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 41 publications
0
6
0
1
Order By: Relevance
“…Modified atmosphere packaging of Oriental melons has been well studied, as they need specific packaging during export and storage because of their short shelf-life and susceptibility to cold-induced damage [ 14 ]. Vessel transportation is readily selected for the export of Oriental melons because of the low cost of transportation, but it takes 3–10 days longer than air transportation, leading to increased decay [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Modified atmosphere packaging of Oriental melons has been well studied, as they need specific packaging during export and storage because of their short shelf-life and susceptibility to cold-induced damage [ 14 ]. Vessel transportation is readily selected for the export of Oriental melons because of the low cost of transportation, but it takes 3–10 days longer than air transportation, leading to increased decay [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Vessel transportation is readily selected for the export of Oriental melons because of the low cost of transportation, but it takes 3–10 days longer than air transportation, leading to increased decay [ 36 ]. Using polyethylene (PE) film and X-tend modified atmosphere (MA)/modified humidity film for Oriental melons at 4 °C and 10 °C for 14 days was found to prolong the shelf-life and reduce the browning of the fruit during storage [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Park and colleagues observed the area of melon fruit surface groove histologically and found that the volume and tightness of melon epidermal cells had changed during cold storage. The groove area on the fruit surface destroys the cuticle, reduces the protection of epidermal wax, and accelerates the browning of the pericarp ( Park et al, 2020 ). The fruit surface groove also has a significant negative correlation with fruit cracking, and melon with fsg does not easily crack.…”
Section: Introductionmentioning
confidence: 99%
“…Para la tecnología de AM, el producto se envasa en una película plástica. La reducción del O 2 o los niveles elevados de CO2 en el interior del paquete, pueden reducir la producción de etileno, retrasar el ablandamiento y ralentizar varios cambios en la composición relacionados con la maduración (Park et al, 2020). La permeabilidad del paquete, la respiración del producto y el riguroso control de la temperatura y la humedad relativa, son los principales factores de interacción a considerar para garantizar la fiabilidad del envasado en AM (Tano et al, 2007;Paulsen et al, 2018).…”
Section: Atmósferas Modificadas (Am) Y Controladas (Ac)unclassified